COMPARATIVE ANALYSIS OF SHARIA AND NON-SHARIA STOCK PORTFOLIO PERFORMANCE IN 2012-2019 - Heike Hakim; Amalia Kusuma Wardini; Lela Nurlaela Wati (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2020)
This study aims to compare the performance of sharia listed in Jakarta Islamic Index, and non-sharia stock portfolio listed in LQ-45 index, whether there is significant difference or not, during the period of January 2012 to December 2019. Although number of sharia stocks dominated Indonesia Stock Exchange, level of literacy index of the Indonesian people in general towards the capital market, especially sharia capital market, is still low. This phenomenon drives this study in analyzing sharia portfolio in order to contribute to increasing the level of literacy index. This is a quantitative research using comparative and descriptive study. The analysis measurement is using portfolio return and risk-adjusted measure such as Treynor and Jensen method, and statistical tests such as one sample t-test and independent sample t-test. The samples were selected using purposive sampling, and populations are stocks listed in Jakarta Islamic Index and stocks listed in LQ-45 index. The result indicates that there is no significant different between sharia and non-sharia stock portfolio performance.